PENGARUH MEDIA KINTAR TERHADAP KEMAMPUAN KEAKSARAAN AWAL ANAK USIA 5-6 TAHUN DI TK TUNAS REMAJA SURABAYA - Utari Safitri; Aisyah Aisyah; Ervin Nurul Affrida (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
This research is motivate by the problem that the early literacy abilitie of children age 5-6 years are still not developed. This is because the teacher only uses the lack of media, namely teaching materials for children's worksheets, so that children feel bored and less enthusiastic. Therefore, researchers make creative media, namely KINTAR media (Kincir Pintar). Media KINTAR (Kintar Pintar) is a game media that is made to resemble a windmill made of plywood or wood with the symbol of the letters (a) to (z) in various colors and attractively decorated. The motivation of this study was to determine the effect of KINTAR media on the early skills of children aged 5-6 year in TK Tunas Remaja Surabaya. The exam strategy used is a quantitative exploration technique with the design of